Silent Period of Masticatory Cycles in Dentate Subjects and Complete Denture Wearers - Goiato, Marcelo Coelho [UNESP]; Garcia, Alicio Rosalino [UNESP]; Santos, Daniela Micheline dos [UNESP]; Zuim, Paulo Renato Junqueira [UNESP]; Marcal Mazza Sundefeld, Maria Lucia [UNESP]; Pesqueira, Aldieris Alves [UNESP] (Wiley-Blackwell, 2011)
Purpose: The purpose of this study was to assess, through electromyographic activity (EMG), the silent period (SP) of masseter and anterior temporal muscles in dentate subjects (DS) and complete denture wearers (CDW).Materials and Methods: The evaluations were performed at the initial and final period of the mastication for the DS group. For the CDW group, the evaluations were performed at the initial period of mastication, with old complete dentures worn for more than 10 years (OCDW) and at the final period of the mastication with new complete dentures (NCDW), 5 months after rehabilitation. Twenty-four asymptomatic subjects (12 DS, 12 CDW) answered a questionnaire based on the Research Diagnostic Criteria for temporomandibular disorders. The CDW group answered the questionnaire before and after new denture insertion and after 5 months of rehabilitation. The SP of the muscles was recorded through EMG at the initial and final periods of mastication using artificial food (Optocal). The operator monitored 35 chewing cycles performed to grind the artificial food and selected eight open-close-clench-chewing cycles for the record.Results: The SP of the muscles analyzed with new complete dentures showed no statistical difference in comparison to the old dentures. There was a statistically significant difference in the SP between the CDW and DS groups for initial and final chewing.Conclusion: Lowered muscular capacity and ability reduced the SP of muscles after rehabilitation with NCDWs.
Keywords: Silent period; mastication; complete denture